Adaptation of Indian and Malay Culture in Muslim Indian Community in Medan City - NURAINI PANGARIBUAN (The Department of Islamic History and Culture in cooperation with the Center for Islamic History and Culture in Aceh and Malay World Studies (PUSAKA), Universitas Islam Negeri Ar-Raniry Banda Aceh, Aceh, Indonesia, 2025)
This research seeks to portray an outline of the description of Indian and Malay cultural adaptation carried out by Muslim Indians in Medan City. The purpose of this research is to see how the process of the Muslim Indian ethnic community makes cultural adaptations in order to maintain their cultural identity and integrate with the local culture (Malay) in Medan city. This research is a social and cultural history research, using library research method and anthropological approach. The results of this study indicate that since the beginning of his arrival to the city of Medan ethnic Indian Muslims received a warm welcome and the adaptation process went well, this is because the ethnic Indian Muslims who came to the city of Medan tried to blend in quickly and did not accentuate their identity (as Indians) thickly even they were able to assimilate into anything and anyone many who assimilated into Malay, Bugis, Javanese and others it was done through the marriage process. The patterns of life of the local community are successfully followed so that there is a very close bond of brotherhood and ethnic Indian Muslims do not look like foreign immigrants in Medan city. In addition, through the Tepung Tawar tradition which is one of the traditions of Indian origin which can then be accepted by the Malay community in Medan city and even become one of the traditions that have been attached to the Malay community, the steps taken by ethnic Indian Muslims at that time by eliminating Hindu elements and embedding Islamic values in it, so that the cultural adaptation process carried out by ethnic Indian Muslims in Medan city is considered successful.